Reflections on social work in practice: Perceptions of how being from a higher caste affects social work among the lower (Dalit) caste people of Nepal (Journal of Comparative Social Work, 2011)
This essay reflects on my community work in a rural village located approximately 70 km from Kathmandu in Nepal. As a social worker, my task was to help integrate people from the Dalit (lower) caste in their local community. The assignment proved to be a challenge, not only because I lacked practical knowledge but also because I belonged to a different caste group, the so-called Brahmin, i.e. the upper caste. In this essay, I discuss how the fact that I am from an upper caste affected my work. The essay attempts to bring forth the problems that I encountered, particularly the critical incidents, and my critical reflections on being a social worker.